Representing Colonial Violence: Trafficking, sex work, and the violence of law - Hunt, Sarah (Atlantis)

(untitled) (Mount Saint Vincent University, 2015)
This article examines the emergence of the discourse on “domestic trafficking” of Indigenous girls and women for the purpose of sexual exploitation. Drawing on community-based experience, the author argues that the shift toward the language and framework of “human trafficking” to capture a range of offences and injustices facing Indigenous women is one of many efforts to recategorize violence against Indigenous women as worthy of legal response in the context of ongoing colonial legal violence.